Gift-exchange in society and the social integration of refugees: Evidence from a field, a laboratory, and a survey experiment - Sabrina Jeworrek; Bernd Josef Leisen; Vanessa Mertins (Halle Institute for Economic Research (IWH), 2020)
Refugee integration requires broad support from the host society, but only a minority of the host population is actively engaged. Given that most individuals reciprocate kind behaviour, we examine the idea that the proportion of supporters will increase as a reciprocal response to refugees' contributions to society through volunteering. Our nationwide survey experiment shows that citizens' intentions to contribute time and money rise significantly when they learn about refugees' pro-social activities. Importantly, this result holds for individuals who have not been in contact with refugees. We complement this investigation with experiments in the lab and the field that confirm our findings for actual behaviour.
urn:nbn:de:gbv:3:2-127005
Keywords: C91; C93; D63; D64; D91; J15; 330; gift-exchange; reciprocity; refugees; integration; field experiment; laboratory experiment